A novel test rig to investigate under-platform damper dynamics. (1st February 2018) - Botto, Daniele; Umer, Muhammad
Highlights: The rig measures contact forces on two dampers dynamically coupled with a blade. Both static and dynamic contact forces affect the blade response. Scatter of dynamic response of the blade is explained with the contact conditions. Abstract: In the field of turbomachinery, vibration amplitude is often reduced by dissipating the kinetic energy of the blades with devices that utilize dry friction. Under-platform dampers, for example, are often placed in the underside of two consecutive turbine blades. Dampers are kept in contact with the under-platform of the respective blades by means of the centrifugal force. If the damper is well designed, vibration of blades instigate a relative motion between the under-platform and the damper. A friction force, that is a non-conservative force, arises in the contact and partly dissipates the vibration energy. Several contact models are available in the literature to simulate the contact between the damper and the under-platform. However, the actual dynamics of the blade-damper interaction have not fully understood yet. Several test rigs have been previously developed to experimentally investigate the performance of under-platform dampers. The majority of these experimental setups aim to evaluate the overall damper efficiency in terms of reduction in response amplitude of the blade for a given exciting force that simulates the aerodynamic loads. Unfortunately, the experimental data acquired on the blade dynamics do not provide enough information to understand the damper dynamics. Therefore, the uncertainty on the damper behavior remains a big issue. In this work, a novel experimental test rig has been developed to extensively investigate the damper dynamic behavior. A single replaceable blade is clamped in the rig with a specific clamping device. With this device the blade root is pressed against a groove machined in the test rig. The pushing force is controllable and measurable, to better simulate the actual centrifugal load acting on the blade. Two dampers, one on each side of the blade, are in contact with the blade under-platforms and with platforms on force measuring supports. These supports have been specifically designed to measure the contact forces on the damper. The contact forces on the blade are computed by post processing the measured forces and assuming the static equilibrium of the damper. The damper kinematics is rebuilt by using the relative displacement, measured with a differential laser, between the damper and the blade under-platform. This article describes the main concepts behind this new approach and explains the design and working of this novel test rig. Moreover, the influence of the damper contact forces on the dynamic behavior of the blade is discussed in the result section.